Determinants of Diabetes Mellitus Among Women Aged 15–49 Years in The Pakutandang Health Center Area, Bandung Regency - Ahmad Zaelani; Yuliana Ruhmania (STIKes Budi Luhur Cimahi, 2026)
Diabetes is one type of non-communicable disease and has become a serious global health issue, including in the Republic of Indonesia. According to Riskesdas data, 70% of people with diabetes mellitus are unaware that they have the disease, partly due to their instant lifestyle. Individuals at risk of developing diabetes include those with genetic or hereditary factors, older age, obesity, hypertension, and a lack of physical activity. The objective of this study is to determine of diabetes mellitus among women of reproductive age (15–49 years) in the service area of the Pakutandang Community Health Centre in Bandung Regency. This study used a quantitative method with a case-control design. Data collection techniques used questionnaires. The population in this study was all women in the working area of the Pakutandang Community Health Centre in Bandung Regency. The sample size was 135 respondents with a 1:2 ratio, namely 45 respondents who were women of childbearing age (15-49 years) with diabetes mellitus and 90 respondents who were women of childbearing age (15-49 years) without diabetes mellitus. The data in this study were processed using univariate analysis, bivariate analysis, and multivariate analysis. The results of this study show that among women of childbearing age (15-49 years), 35.5% had diabetes mellitus and 64.5% did not have diabetes mellitus. The results of the bivariate chi-square analysis showed that the factors associated with diabetes mellitus were education, occupation, genetic factors, age, hypertension, and physical activity, while obesity was not associated. The conclusion of this study is that the occurrence of diabetes mellitus in women of childbearing age (15-49 years) influenced by genetic factors, and this influence significant in the occurrence of diabetes mellitus in women of childbearing age (15-49 years). Meanwhile, the logistic regression results show that the dominant variable is genetic factors.